Marketing Strategies of the Banking Industry: Evolution and Impact of Marketing in the Indian Banking Industry (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Marketing  came into  Indian  banks in  the  late 1950's  not  in the  form  of marketing concept but in the forms ofadvertising and promotion concept. Soon it was realised that marketing transcendsadvertising and friendliness. Till 1950 it was recognised that personal sellingwas not necessaiy. The bankers went out of their way to avoid being accused ofselling. The bankers even eliminated the word 'selling' and they called thefunction of customer contact 'business development function.